Computational Strategies Targeting Inhibition of Helicobacter pylori and Cryptococcus neoformans Ureases - Fabris, Marciéli; Nascimento-Júnior, Nailton M. [UNESP]; Bispo, Marcelle L. F.; Camargo, Priscila G. (Bentham Science Publishers, 2023)
Helicobacter pylori and Cryptococcus ssp. are pathogenic ureolytic microorganisms that cause several disorders in the host organism and, in severe cases, lead to death. Both infections have the urease enzyme as a key virulence factor since they use its ability to produce ammonia to soften the inhospitable pH to which they are subjected. In this review, we describe two ureases as possible molecular targets for drug discovery and provide insights for developing potent inhibitors against ureases from these pathogenic microorganisms through computer-aided drug discovery approaches, such as structure-based drug design (SBDD) and structure-activity relationship (SAR). The SAR studies have indicated several essential subunits and groups to be present in ure-ase inhibitors that are critical for inhibitory activity against H. pylori or Cryptococcus spp. Since the three-dimensional structure of C. neoformans urease has yet to be determined experimentally, the plant urease of Canavalia ensiformis was used in this study due to its structural similarity. Therefore, in the SBDD context, FTMap and FTSite analyses were performed to reveal characteristics of the urease active sites in two protein data bank files (4H9M, Canavalia ensiformis, and 6ZJA, H. pylori). Finally, a docking-based analysis was performed to explore the best inhibitors described in the literature to understand the role of the ligand interactions with the key residues in complex ligand-urease stabilization, which can be applied in the design of novel bioac-tive compounds.
Keywords: Canavalia ensiformis; cryptococcosis; Drug discovery; molecular docking; structure-activity relationship; urease inhibitors; ureolytic microorganisms; virulence factor